2021
DOI: 10.1016/j.jad.2021.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Association between perceived stress and depression among medical students during the outbreak of COVID-19: The mediating role of insomnia

Abstract: Background The purpose of this study was to explore the association between perceived stress and depression among medical students and the mediating role of insomnia in this relationship during the COVID-19 pandemic in China. Methods A cross-sectional survey was conducted from March to April 2020 in medical university. Levels of perceived stress, insomnia and depression were measured using Perceived Stress Scale (PSS), Insomnia Severity Index (ISI) and Patient Health Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
50
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 73 publications
10
50
0
12
Order By: Relevance
“…Our result that perceived stress made an important contribution to the anxiety and depressive symptoms was also consistent with previous studies both during ( 49 ) and before ( 19 , 20 ) the outbreak in students and other populations ( 50 , 51 ). In the current study, the only psychological variable in the regression was perceived stress.…”
Section: Discussionsupporting
confidence: 93%
“…Our result that perceived stress made an important contribution to the anxiety and depressive symptoms was also consistent with previous studies both during ( 49 ) and before ( 19 , 20 ) the outbreak in students and other populations ( 50 , 51 ). In the current study, the only psychological variable in the regression was perceived stress.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, Spanish college students aged between 18 and 42 years old were also found to have insomnia associated with symptoms of depression, anxiety, and stress during the pandemic [48]. Finally, a study conducted during the pandemic on medical students in China confirmed the association between insomnia, perceived stress, and depression [49]. Thus, cognitive behavioral therapy for insomnia (CBT-I) has been found as an effective therapy in reducing insomnia and improving sleep quality.…”
Section: Discussionmentioning
confidence: 92%
“…A meta-analysis conducted by Zhai et al indicated that both short and long sleep duration were significantly associated with an increased risk of MDD in adults [83]. Recently, Liu et al showed that insomnia mediated the association between perceived stress and depression but did not affect perceived stress directly [84]. These results suggest that insomnia could be a medical condition on its own, rather than a symptom of depression, and that improving sleep conditions could attenuate or prevent stress-induced depressive symptoms.…”
Section: Sleep Disordersmentioning
confidence: 99%